Acute kidney injury definition following PCI and cardiovascular outcomes. (14th October 2021) - Skalsky, K; Levi, A; Bental, T; Vaknin-Assa, H; Assali, A; Steinmetz, T; Kornowski, R; Perl, L
Abstract: Background: Acute kidney injury (AKI) is a complication of percutaneous coronary intervention (PCI), known to increase rates of adverse medical events. We aimed to identify the optimal definition of AKI in predicting of adverse cardiovascular outcomes and mortality post PCI. Methods: From a large registry of patients undergoing PCI between 2006–2018 (n=25, 690) at two hospitals, consecutive patients were assessed for the presence of AKI according to four different definitions: a relative elevation of ≥25% or ≥50%; or an absolute elevation of ≥0.3 mg/dL or ≥0.5 mg/dL in serum creatinine at 48 hours post PCI. We assessed the calculated rates of AKI according to the different definitions. The discriminant capacity for 30-day and 1-year mortality and MACE (MACE: all-cause death, myocardial infarction, target-vessel revascularization and coronary artery bypass graft surgery) of each definition was calculated using ROC curves and AUCs. Results: Data of 15, 153 patients was available for final analysis. Rates of AKI were 12.1%, 3.2%, 8.1% and 3.9% according to the four definitions, respectively. The discriminant capacity of adverse outcomes was highest among those defined as AKI according to the third definition - an absolute elevation of ≥0.3 mg/dL in serum creatinine with an AUC of 0.82 (95% CI 0.80–0.84) for 30-day mortality (P value = 0.036) and an AUC of 0.78 (CI 0.76–0.79) for 30 days MACE. Conclusions: An absolute elevation of ≥0.3 mg/dL in serum creatinine 48 hours post PCI predicts overall mortality and MACE most accurately. FUNDunding Acknowledgement: Type of funding sources: None.